lncRNA GAS5/miR-452-5p Reduces Oxidative Stress and Pyroptosis of High-Glucose-Stimulated Renal Tubular Cells - Xie C; Wu W; Tang A; Luo N; Tan Y (Diabetes, Metabolic Syndrome and Obesity, 2019)
Cuisong Xie,1 Weiling Wu,1 Ainan Tang,2 Ning Luo,1 Yanfei Tan1 1Department of Endocrinology, Chenzhou No.1 People’s Hospital, Chenzhou, Hunan 423000, People’s Republic of China; 2Department of Endocrinology, Chenzhou 3rd People’s Hospital, Chenzhou, Hunan 423000, People’s Republic of ChinaCorrespondence: Cuisong XieDepartment of Endocrinology, Chenzhou No.1 People’s Hospital, 102 Xijie Street, Beihu District, Chenzhou, Hunan 423000, People’s Republic of ChinaEmail xcszgr@163.comBackground: Diabetic nephropathy (DN) is the leading cause of end-stage renal failure worldwide. lncRNAs are demonstrated to improve the DN by changing the expression of miRNAs. This study was aimed to investigate the effect of lncRNA GAS5/miR-452-5p on the inflammation, oxidative stress and pyroptosis of high-glucose-induced renal tubular cells.Methods: HK-2 cells were induced by HG to simulate DN cells. RT-qPCR analysis confirmed the transfection effects and detected the expression of GAS5, NLRP3, caspase1, IL-1β, pro-caspase1, pro-IL-1β, GSDMD-N and miR-452-5p. Western blot analysis determined the protein expression of NLRP3, caspase1, IL-1β, pro-caspase1, pro-IL-1β and GSDMD-N. The expression of GSDMD-N was also verified by immunofluorescence. The levels of TNF-α, IL-6, MCP-1, ROS, MDA and SOD were measured by commercial assay kits, respectively. Dual-luciferase reporter assay indicated that GAS5 could combine with miR-452-5p.Results: GAS5 expression was decreased in HG-induced HK-2 cells. GAS5 overexpression could decrease the levels of TNF-α, IL-6, MCP-1, ROS and MDA and increase the levels of SOD. Moreover, GAS5 overexpression suppressed the expression of NLRP3, caspase1, IL-1β and GSDMD-N, and the results of immunofluorescence verified the above results. miR-452-5p interference could cause the same changes as GAS5 overexpression for HG-induced HK-2 cells, and GAS5 inhibition could reverse the effect of miR-452-5p interference.Conclusion: GAS5 overexpression inhibited the inflammation, oxidative stress and pyroptosis of HG-induced renal tubular cells by downregulating the expression of miR-452-5p.Keywords: lncRNA GAS5, miR-452-5p, oxidative stress, pyroptosis, high glucose, renal tubular cells